(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Objectives:To study the effect of Metformin induced Vitamin B12 deficiency among patients with Type 2 diabetes mellitus (T2DM). Design:Case - control study. Setting:Outpatient clinics of Diabetic Endocrine Research Lab and patients reporting to medicine department of Sheth Vadilal Sarabhai General Hospital ( Smt. NHL Municipal Medical College ) , Ahmedabad, Gujarat .Participants:A total of 240 patients, 100 control group healthy normal and nondiabetic 140 study group with Type 2 Diabetes treated with Metformin and not known with a contraindication for the use of Metformin were approached, given informed consent, and entered the study. .Intervention : Addition of Metformin to Insulin Therapy three times a day. Primary Outcomes :Vitamin B12, Folic acid ,Serum Homocysteine. Results :Compare with control, Metformin Treatment was associated with a mean difference in Vitamin B12 -340.26 and confidence 6.71 ( 95 % confidence interval 27.53 to 40.95 : P= < 0.0001) , and 1 in Folate concentration of - 6.24 and confidence 0.18 ( 95% confidence interval 0.74 to 1.1: P=0.026 ) , and an increase in Homocysteine concentration of 18.97 and confidence 0.93 ( 95% confidence interval 3.83 to 5.69 : P= < 0.0001 ) . In addition, decrease Vitamin B12 and Folate could be explained by the increase in Homocysteine. Conclusion :Metformin increases the risk of Vitamin B12 deficiency and Folate, which results in a modest increase in Homocysteine concentration among patients with Type 2 Diabetes. Vitamin B12 Deficiency is preventable , therefore our findings suggests that regular measurements of Vitamin B12 during long term Metformin treatment should be strongly considered .